Applied architecture patterns on the Microsoft platform : work with various Microsoft technologies using applied architecture patterns - Dovgal, Andre; Noriskin, Gregor; Olechko, Dmitri (Packt Publishing, 2014)
Presented in a scenario-driven tutorial way, we lead you through fictitious example problems and present you with the best solutions. This book is intended for architects, developers, and managers who need to improve their knowledge of the Microsoft application platform. This book will appeal to anyone, especially consultants, who want to get up to speed on selecting the most appropriate platform for a particular problem. A good understanding of the general Windows platform and development technologies would be helpful.
Title from PDF title page (viewed on August 14, 2014).
Keywords: Software architecture -- Evaluation.; Microsoft software -- Evaluation.; Business enterprises -- Computer networks -- Planning.; elektronické knihy; electronic books